(untitled) (Journal of the College of Basic Education, 2019)
Pycnogenol pinus pinaster Ait ( a water extract of polyphenolic compounds ) was extracted from Iraqi pine bark and analyzed using high performance liquid chromotography (HPLC) coupled to ultra violet UV detection that was recorded at (254 nm). Pycnogenol action on some biochemical parameters (glucose , total cholesterol (TC) , triacylglycerol (TG) , high density lipoproteins (HDL) ,low density lipoproteins (LDL) , very low density lipoproteins (VLDL) )level was determined in (30) type -2- diabetic patients who treated with capsules (500 mg) of pycnogenol three times daily to examine the reactive role of pycnogenol against oxidative stress.The above biochemical parameters were measured in plasma before treatment with pycnogenol and after (1 week) , (2 weeks) and (3 weeks) of treatment with this polyphenolic extract. Our results have shown that glucose level was increased relatively for diabetic patients compared with control group (p<0.001) but after treatment with pycnogenol , glucose level would be decreased relatively (p<0.001) after (1 week) , (p<0.001) after (2 weeks) and (p<0.05) after (3 weeks) of treatment with pycnogenol.Total cholesterol (TC) level increased relatively for diabetic patients compared with control group (p<0.001) , but after treatment with this reactive extract (TC) level decreased relatively (p<0.001) after (1 week) , (p<0.001) after (2 weeks) and (p<0.01) after (3 weeks) of treatment with pycnogenol.Triacylglycerol (TG) level was increased relatively for diabetic patients compared with control group (p<0.001) , but after treatment with this antioxidant extract (TG) level decreased relatively (p<0.001) after (1 week) , (p<0.001) after (2 weeks) and (p<0.01) after (3 weeks) of treatment with pycnogenol.High density lipoproteins (HDL) level was decreased relatively for diabetic patients compared with control group (p<0.001) , but after treatment with pycnogenol (HDL) level increased relatively (p<0.01) after (1 week) , (p<0.01) after (2 weeks) and (p<0.05) after (3 weeks) of treatment with pycnogenol.Low density lipoproteins (LDL) level increased relatively for diabetic patients compared with control group (p<0.001) , but after treatment with pycnogenol , (LDL) level decreased relatively (p<0.001) after (1 week) , (p<0.001) after (2 weeks) and (p<0.01) after (3 weeks) of treatment with pycnogenol. Very low density lipoproteins (VLDL) level increased relatively for diabetic patients compared with control group (p<0.001) , but after treatment with pycnogenol , (VLDL) level decreased relatively (p<0.001) after (1 week) , (p<0.001) after (2 weeks) and (p<0.01) after (3 weeks) of treatment with pycnogenol.